Broodstock conditioning, spawning, embryonic and early larval development of a novel baby clam species for aquaculture in the southeast Pacific: Tawera elliptica (Lamarck, 1818). (1st February 2021) - Barría, Camila; Abarca, Alejandro; Colivoro, David; Célis, Angela; Couve, Pablo; Cárcamo, Daniel; Durán, L. René; Oliva, Doris
Abstract: Tawera elliptica is a small size (baby) clam with an export fishery in southern Chile. The species is dioecious with external fertilization and without sexual dimorphism. The aim of this work was to optimize broodstock conditioning, induce spawning and describe embryonic development until the early larval stage in a hatchery. Broodstock were conditioned at 3 treatments (with/without sand; water circulation) for 48 days. The clams were fed with a mixed diet of macroalgae, with a daily ration of 250, 000 cells/ml. Broodstock response was quantified using condition index and gonad development stages (histological techniques). For spawning induction, physical and biological methods were tested. The best response was achieved in males with physical induction. Histological analysis showed that the water circulation system treatment exhibited the highest percentage of maximum maturity. A fertilization ratio of 500:1 sperm:oocyte was used. The incubation was carried out in 3‐L containers with filtered seawater at 10.7 ± 0.9°C without aeration. Observations, measurements and the duration of each embryonic and larval stage were recorded. The oocyte has a prominent gelatinous layer (= jelly coat) that disappears between the gastrula and trochophore stages. The status of the D‐larval stage was reached at 107 h post fertilization with a mean valve length of 91.4 ± 8.9 µm. This is the first record of the complete embryonic development of this baby clam until the early larval stage and the conditioning in a water circulation system for 48 days are suitable for the species.